2015
DOI: 10.1111/infi.12074
|View full text |Cite
|
Sign up to set email alerts
|

Has the Transmission of Policy Rates to Lending Rates Changed in the Wake of the Global Financial Crisis?

Abstract: Central banks of major advanced economies have maintained a very accommodative monetary policy stance in the last few years. However, concerns have surfaced that the transmission of low policy rates to lending rates has been weaker than in the past. Has the transmission of policy rates to lending rates been impaired by the global financial crisis? To answer this question, we first estimate standard cointegrating equations linking policy and lending rates for non-financial firms in Italy, Spain, the United King… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 29 publications
2
43
0
2
Order By: Relevance
“…Despite much debt being fixed rate, it is assumed that there is full pass‐through as there is scope to renegotiate mortgages. In practice, reductions in debt interest payments may be smaller than in the simulations, potentially changing the sign of the net effect in some countries, and there is evidence that pass‐through has decreased since the financial crisis (Gambacorta, Illes, & Lombardi, ).…”
Section: Effects Of Monetary Policy On Inequalitymentioning
confidence: 95%
“…Despite much debt being fixed rate, it is assumed that there is full pass‐through as there is scope to renegotiate mortgages. In practice, reductions in debt interest payments may be smaller than in the simulations, potentially changing the sign of the net effect in some countries, and there is evidence that pass‐through has decreased since the financial crisis (Gambacorta, Illes, & Lombardi, ).…”
Section: Effects Of Monetary Policy On Inequalitymentioning
confidence: 95%
“…Ji et al () have also suggested that certain institutional factors impede the effectiveness of interest rate pass‐through, such as the still relatively large volatilities of FR007, the underdeveloped state of China's derivative securities market, and the fact that most Chinese banks still mainly rely on deposits as their funding source. However, from a dynamic viewpoint, as Gambacorta et al () have argued, this lower pass‐through seems to be related in part to the higher premium for risk required by banks and by the worsening of their financial condition as well. The Chinese economy has been facing downward pressure since 2015, by the end of which economic growth had cooled to a 25‐year low.…”
Section: Discussionmentioning
confidence: 99%
“…But examination of the lending rates reveals they did not fall that much (Illes and Lombardi 2013;Gambacorta et al 2014). In fact, the margins over policy rates have widened as policy rates have fallen (Fig.…”
Section: The Fragmentation Of the European Financial System Along Natmentioning
confidence: 99%
“…13 The literature on the pass-through of monetary policy to lending rates is vast. From an empirical point of view, a recent paper by Gambacorta et al (2014) investigates the pass-through of monetary policy to lending rates applied to nonfinancial firms in major advanced economies, prior and after the global Great Crisis. They find evidence of a structural break after Lehman Brothers' default, due to a strong increase in the markup between the lending rate and the policy rate of central banks, both in the USA and in Europe.…”
Section: The Fragmentation Of the European Financial System Along Natmentioning
confidence: 99%